KIBLAT DALAM PERSPEKTIF MADZHAB- MADZHAB FIQH - Sayful Mujab (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Astronomy is a science which deals with the subject of at least four aspects related to worship i.e. the qibla, prayer time, the beginning of the months of Qamariah, and eclipses, both sun and moon. Each of the four subjects has legal foundations that have been discussed by the scholars. This article will discuss about qibla in the perspective madzhab. What is qibla has been debated among madzhab’s expert, which raises two major opinions. The opinions are whether the qibla is the physical building of the Kaaba or whether it is the direction of the Kaaba building. This is because there are two Hadith which in dzahir looks different which cause such differences.Keywords: qibla, madzhab, different, opinion.